Synthesis of 2,2'-Biindole: Formal Synthesis of Arcyriaflavin-A and Staurosporinone (K-252c) - Parvatkar, P.T.; Kadam, H.K.; Parameswaran, P.S.; Tilve, S.G. (Asian Journal of Chemistry, 2012)
A convenient four-stage synthesis of 2,2'-biindole, the immediate precursor of arcyriaflavin A and staurosporinone via double Wittig-double reductive cyclization reactions is described.